Tetra-aqua-(4,4'-bimethyl-2,2'-bipyridine)-nickel(ii) sulfate hydrate: a simple structure with an extremely complex H-bonding scheme. - Suarez, Sebastian (2013)
The title ionic compound, [Ni(C12H12N2)(H2O)4]SO4H2O, is composed of an NiII cation coordinated by a chelating 4,40- dimethyl-2,20-bipyridine ligand via its two N atoms [mean Ni?N = 2.056 (2) A ˚ ] and by four aqua ligands [mean Ni?O = 2.073 (9) A ˚ ], the net charge being balanced by an external sulfate anion. The whole structure is stabilized by a solvent water molecule. Even though the individual constituents are rather featureless, they generate an extremely complex supramolecular structure consisting of a central hydrogenbonded two-dimensional hydrophilic nucleus made up of complex cations, sulfate anions and coordinated and solvent water molecules, with pendant hydrophobic 4,40-dimethyl-2,20- bipyridine ligands which interact laterally with their neighbours via ? interactions. The structure is compared with closely related analogues in the literature.